The impact of Facebook on social image, interaction skills and discourse: a case study of UniKL MICET students / Mariati Mohd Salleh - Mohd Salleh, Mariati (2012)
With 900 million account holders, it is without doubt that Facebook is the most popular social networking site the world has ever witnessed. The users come from all walks of life, without any discrimination on gender, ethnicity, age, religion or political affiliation - it is a cyber-state with citizens that can present themselves, their views and ideas to a select circle of friends, not strangers. Considered a dominant, vibrant social networking site (Khaddage & Bray, 2011) in youths’ life today, Facebook allows its users to be the “centre of the world” in their own space (Dalsgaard, 2008, p.9). The study focuses on the impact of Facebook to its users’ social image, interaction skills and discourse. The research utilized a set of questionnaire as the instrument to measure the influence and role that Facebook plays on 136 young undergraduates in UniKL MICET, Melaka. The findings of the study is very interesting as it can be perceived that Facebook does influence the construction of a positive social image of its participants, as many respondents claim that they will only reveal the positive side of themselves to their Facebook audience. Other than that, it is observed that Facebook has helped the undergraduates improve their interaction skills, especially with friends and relatives they were not familiar with before. Finally, it is also perceived from the findings that Facebook influences the use of discourse among the respondents, who feel that their English proficiency has improved due to the frequent use of the language on the social network. Therefore, it is hoped that with the findings, educators can engage young Facebookers to utilize the social network through activities that can improve their social image, interaction skills and discourse